2019
DOI: 10.1177/2325967118824551
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Pectoralis Major Muscle Ruptures: A Systematic Review and Meta-analysis

Abstract: Background:Pectoralis major muscle (PMM) tendon ruptures are becoming more common. Multiple techniques for fixation of the avulsed tendon to its humeral insertion have been described. None of these techniques has been reviewed to compare outcomes in efforts to establish a first-line surgical technique.Purpose:To systematically review and analyze the data available in the literature to establish a clinically superior surgical technique and time frame in which surgery should occur.Study Design:Systematic review;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 73 publications
0
45
0
4
Order By: Relevance
“…In a large recent meta-analysis of 20 articles with 384 patients, Bodendorfer et al 5 reported that functional outcomes and cosmetic satisfaction were significantly superior in acute versus chronic repairs. However, Gupton and Johnson 10 reported no differences between acute and chronic repairs in another similar study of 259 patients. Our findings would support previous studies in that acute repair resulted in better functional outcomes and return of strength than chronic repair in an active, young, high-demand population.…”
Section: Discussionmentioning
confidence: 89%
“…In a large recent meta-analysis of 20 articles with 384 patients, Bodendorfer et al 5 reported that functional outcomes and cosmetic satisfaction were significantly superior in acute versus chronic repairs. However, Gupton and Johnson 10 reported no differences between acute and chronic repairs in another similar study of 259 patients. Our findings would support previous studies in that acute repair resulted in better functional outcomes and return of strength than chronic repair in an active, young, high-demand population.…”
Section: Discussionmentioning
confidence: 89%
“…Pectoralis major tendon ruptures are rare injuries but have been increasing in prevalence with the rising popularity of weight training and lifelong fitness [1,2,6]. Most commonly, rupture of this tendon occurs in males between the ages of 20-40 years-old and often happens while performing the bench press, a popular exercise for many weightlifters [1,2,6]. In this case, the inciting incident was not the bench press or any other less-commonly reported mechanism, but rather unusual in that it was associated with an exercise performed during a CrossFit workout.…”
Section: Discussionmentioning
confidence: 99%
“…The pectoralis major muscle is a large, broadbased muscle of the upper extremity responsible for adduction, internal rotation and elevation of the glenohumeral joint [1]. The muscle's two portions, the sternocostal head and the clavicular head, combine together then twist to form a common tendon that inserts lateral to the bicipital groove on the proximal humerus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations